Experiences of youth justice: youth justice discourses and their multiple effects - McAlister, S.; Carr, Nicola (Sage, 2014)
Interventions within youth justice systems draw on a range of rationales and philosophies. Traditionally demarcated by a welfare/justice binary, the complex array of contemporary rationales meld different philosophies and practices, suggesting a mutability that gives this sphere a continued (re)productive and felt effect. While it may be increasingly difficult to ascertain which of these discourses is dominant in different jurisdictions in the UK, particular models of justice are perceived to be more prominent (Muncie, 2006). Traditionally it is assumed that Northern Ireland prioritises restoration, Wales prioritises rights, England priorities risk and Scotland welfare (McVie, 2011; Muncie, 2008, 2011). However, how these discourses are enacted in practice, how multiple and competing rationales circulate within them and most fundamentally how they are experienced by young people is less clear. This paper, based on research with young people who have experienced the full range of interventions in the youth justice system in Northern Ireland examines their narratives of ‘justice’. It considers how different discourses might influence the same intervention and how the deployment of multiple rationalities gives the experience of ‘justice’ its effect.